Mannan Oligosaccharides Application: Multipath Restriction From Aeromonas hydrophila Infection in the Skin Barrier of Grass Carp (Ctenopharyngodon idella) - Lu, Zhiyuan; Feng, Lin; Jiang, Wei-Dan; Wu, Pei; Liu, Yang; Jiang, Jun; Kuang, Sheng-Yao; Tang, Ling; Li, Shu-Wei; Liu, Xiang-An; Zhong, Cheng-Bo; Zhou, Xiao-Qiu (Frontiers in Immunology, 2021)
The objective of this study was to evaluate the efficacy of dietary Mannan oligosaccharides (MOS) supplementation on skin barrier function and the mechanism of on-growing grass carp (Ctenopharyngodon idella). Five hundred-forty grass carp were fed for sixty days from the growing stage with six different level MOS diets (0, 200, 400, 600, 800, 1000 mg kg-1). At the end of the growth trial, the fourteen days Aeromonas hydrophila challenge experiment has proceeded. The obtained data indicate that MOS could: (1) decline skin lesion morbidity after challenged pathogenic bacteria; (2) maintain physical barrier function via improving antioxidant ability, inhibiting excessive apoptosis, and strengthening the tight junction between the epithelial cell and related signaling pathway (Nrf2/Keap1, p38MAPK, and MLCK); (3) regulate immune barrier function by modulating the production of antimicrobial compound and expression of involved cytokines and related signaling pathway (TOR and NFκB); Finally, we concluded that MOS supplementation reinforced the disease resistance and protected fish skin barriers function under infection of Aeromonas hydrophila.